2015
DOI: 10.1186/s13017-015-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clotting factor activities early after severe multiple trauma and their correlation with coagulation tests and clinical data

Abstract: IntroductionTraumatic injuries are amongst the leading causes of death worldwide, frequently as a result of uncontrolled hemorrhage. Critical deficiencies in clotting factors have been noted in trauma-induced coagulopathy. However, the exact underlying conditions that result in devastating coagulopathies remain unclear. The purpose of this study was to elucidate these underlying deficiencies.MethodsBlood samples were drawn from 45 severely injured trauma patients on their arrival at the resuscitation room, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
5
23
0
1
Order By: Relevance
“…Written informed consent was obtained from the participants. This study expands data from an original prospective study of severely injured patients by minor to moderate multiple trauma victims [ 8 ].…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…Written informed consent was obtained from the participants. This study expands data from an original prospective study of severely injured patients by minor to moderate multiple trauma victims [ 8 ].…”
Section: Methodsmentioning
confidence: 65%
“…Cohen et al, based on a subgroup analysis of data from the PROMMTT-study, demonstrated that clotting factor activities are reduced in coagulopathic major trauma patients receiving blood products [ 7 ]. Furthermore, a moderate reduction of clotting factor activities early after severe multiple trauma, irrespective of patient coagulation status, was shown [ 8 ]. However, all studies excluded a considerable number of patients from the final analysis according to certain patient characteristics (e.g., injury severity).…”
Section: Introductionmentioning
confidence: 99%
“…5 Surgeons consider CF activities less than 30% to be critical as surgical hemostasis appears to be compromised when CF levels fall below 30%. 6 The ASRA guidelines on neuraxial and regional procedures in patients taking anticoagulants, on the other hand, chose CF activities of less than 40% as indicating a significant risk of clinical bleeding. 1 Similar to the ASRA guidelines, we considered CF activities of less than 40% as the cutoff for increased risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of all the coagulation factors is observed, but is especially significant in the case of fibrinogen;29 30 a fibrinogen deficit is observed in 14–26% of all seriously injured patients 31 32. This decrease occurs early after a severe trauma even before any fluid administration 33 34.…”
Section: Haemostatic Resuscitationmentioning
confidence: 99%